2011
DOI: 10.4236/ojog.2011.13020
|View full text |Cite
|
Sign up to set email alerts
|

Labour analgesia effects on foetal heart rate. A mini-review

Abstract: Foetal well-being during labour is of utmost importance. One of the ways to attempt to assess foetal wellbeing is by recording foetal heart rate (FHR). Loss of variability and deceleration patterns are known to be associated with foetal distress. Decelerations and foetal bradycardia have been described after any type of effective labour analgesia. This review addresses the questions if certain analgesic techniques and/or analgesics lead to clinically relevant FHR changes, what is their aetiology, and how we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 67 publications
0
3
0
6
Order By: Relevance
“…In conclusion, the routine prescription and utilization of epidural analgesia by Nigerian obstetrician who is the custodian of women's health is still quite suboptimal, despite the overwhelming high level evidence which has clearly shown that many of fears, unsubstantiated risks, as well as the unfounded myths ascribed to epidural analgesia in labor are baseless and that its benefits far outweigh any risks to both mother and baby (1,8,24,25). Therefore, adequate patient education, training of personnel and subsidization of this service will go a long way in promoting the acceptability and utilization of epidural analgesia for women in labor.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the routine prescription and utilization of epidural analgesia by Nigerian obstetrician who is the custodian of women's health is still quite suboptimal, despite the overwhelming high level evidence which has clearly shown that many of fears, unsubstantiated risks, as well as the unfounded myths ascribed to epidural analgesia in labor are baseless and that its benefits far outweigh any risks to both mother and baby (1,8,24,25). Therefore, adequate patient education, training of personnel and subsidization of this service will go a long way in promoting the acceptability and utilization of epidural analgesia for women in labor.…”
Section: Discussionmentioning
confidence: 99%
“…Не существует единого представления о влиянии регионарной анестезии на частоту сердцебиения плода. По литературным данным, брадикардия и нарушение сердечного ритма возникают у плода при любой эффективной регионарной анестезии в родах (эпидуральной, спинальной и спинально-эпидуральной) при использовании различных местных анестетиков [9]. Некоторые исследователи отмечали кратковременное развитие брадикардии у плода [9,10].…”
Section: Discussionunclassified
“…По литературным данным, брадикардия и нарушение сердечного ритма возникают у плода при любой эффективной регионарной анестезии в родах (эпидуральной, спинальной и спинально-эпидуральной) при использовании различных местных анестетиков [9]. Некоторые исследователи отмечали кратковременное развитие брадикардии у плода [9,10]. Другие находили кратковременные колебания частоты сердцебиения плода и развитие поздних и вариабельных децелераций [11], свидетельствующих об изменении у плода газообмена и возможном развитии гипоксемии/гипоксии [9,[12][13][14].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Despite the clear benefit of pain reduction, management measures should not interfere with the normal birth process. The literature has become increasingly focused on the maternal and fetal effects of intrapartum analgesia 5 , 6 , 7 , although little is known still about the use of i. v. PCA with remifentanil in a German population 8 .…”
Section: Introductionmentioning
confidence: 99%